A kind of high-strength white facing concrete and preparation method thereof

By adopting specific formulas and treatment methods in white finish concrete, the problems of inconsistent color, hollows, cracks and poor carbonization resistance of white finish concrete in the prior art are solved, and high working stability, carbonization resistance and High-strength white finish concrete with beautiful effect.

CN117720317BActive Publication Date: 2025-02-14CHINA WEST CONSTR GRP NEW MATERIAL TECH CO LTD +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311741960.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-18
Publication Date
2025-02-14
Estimated Expiration
2043-12-18

AI Technical Summary

Technical Problem

The existing white-faced concrete has problems such as inconsistent color, hollowness, cracks and poor carbonization resistance during use, which affects the aesthetics and decorative effect.

Method used

Using high-strength white finish concrete formulas, including white cement, white high-active mineral blends, limestone machined sand, limestone gravel, viscosity-reducing admixture, carbonization inhibition auxiliary agent and functional defoaming agent, through specific components The proportion and treatment method form concrete with high mechanical strength and carbonization resistance.

Benefits of technology

It achieves high working stability, carbonization resistance and aesthetic effects of concrete, reduces the existence of bubbles, avoids color inconsistency and structural defects, and meets the needs of low-carbon and green development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004613357200000051
    Figure BDA0004613357200000051
  • Figure BDA0004613357200000061
    Figure BDA0004613357200000061
  • Figure BDA0004613357200000062
    Figure BDA0004613357200000062
Patent Text Reader

Abstract

The present invention discloses a high-strength white facing concrete and a preparation method thereof, and relates to the technical field of building materials; the concrete comprises white cement, white high-activity mineral admixture, limestone machine-made sand, limestone crushed stone, water, viscosity-reducing admixture, carbonation inhibition auxiliary agent and functional defoamer. The present invention also provides a preparation method of the above concrete. The concrete of the present invention has good aesthetic and decorative effects, eliminates the processes of coating and facing, meets the needs of low-carbon green development, and effectively solves the problems of concrete bubbles, inconsistent color, voids, cracks and poor carbonation resistance in the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to high-strength white facing concrete and a preparation method thereof. Background Art

[0002] With the development of social economy, people's requirements for buildings are not limited to basic functions. They have higher and higher requirements for beauty and decoration. White facing concrete is favored by people for its unique appearance. At present, there are more and more white facing concrete buildings. However, in use, on the one hand, due to the unstable workability of concrete, the appearance of the formed structure often has inconsistent color, and problems such as voids and cracks occur frequently. On the other hand, the large number of bubbles introduced into the concrete improves the fluidity of the concrete, but the bubbles on the surface of the structure affect the finishing effect. At the same time, with the changes in the environment and the passage of time, the surface of the white facing concrete is prone to carbonization and the color becomes darker, which affects the appearance. It has to be recolored later, which loses the meaning of pouring the white facing concrete once.

[0003] Therefore, it is of great significance to develop a white facing concrete with high working stability, high carbonation resistance, no bubbles on the surface, beautiful appearance and good decorative effect. Summary of the invention

[0004] In order to solve the above-mentioned technical problems, the purpose of the present invention is to provide a high-strength white facing concrete and a preparation method thereof. The concrete has good aesthetics and decorative effects, eliminates the processes of coating and finishing, meets the needs of low-carbon green development, and effectively solves the problems of concrete bubbles, inconsistent color, voids, cracks and poor carbonation resistance in the prior art.

[0005] The technical solution of the present invention to solve the above technical problems is as follows: Provide a high-strength white facing concrete, including white cement, white high-activity mineral admixture, limestone machine-made sand, limestone crushed stone, water, viscosity-reducing admixture, carbonization inhibition auxiliary agent and functional defoamer;

[0006] The mass ratio of white cement, white high-activity mineral admixture, limestone machine-made sand, limestone crushed stone, water, viscosity-reducing admixture, carbonation inhibition auxiliary agent and functional defoaming agent is 400-480:50-80:580-700:1100-1160:160-164:10.5-12:4-6:0.9-1.2.

[0007] Furthermore, the white cement is white silicate cement, PW-1 42.5, whiteness value ≥89.

[0008] Furthermore, the white high-activity mineral admixture is a solid mixed powder formed by mixing white phosphorus slag powder, white S95 mineral powder and white silica fume in a mass ratio of 20-40:20-50:10-30.

[0009] Furthermore, the water requirement ratio of white high-activity mineral admixture is ≤105%, the 28d activity is ≥90%, and the specific surface area is 480-560m 2 / kg.

[0010] Furthermore, the MB value of limestone machine-made sand is ≤0.8, the fineness modulus is 2.9-3.3, the particle size is less than 80μm ≤3.0%, and the mud content rate is ≤0.1%.

[0011] Furthermore, the limestone crushed stone is continuously graded with a particle size of 5.0-25.0 mm and a mud content of ≤0.1%.

[0012] Furthermore, the viscosity-reducing admixture is prepared by mixing polycarboxylic acid water-reducing mother liquor, polycarboxylic acid phosphate viscosity-reducing mother liquor, polycarboxylic acid medium-term slow-release collapse-preserving mother liquor, polycarboxylic acid late-term slow-release collapse-preserving mother liquor and retarder in a mass ratio of 35-45:20-30:5-10:10-20:10-20. The water-reducing rate is ≥25.0%, and the collapse-preserving time is 4-5h.

[0013] Furthermore, the viscosity-reducing admixture is a polycarboxylic acid water-reducing mother solution, a polycarboxylic acid phosphate viscosity-reducing mother solution, a polycarboxylic acid intermediate-term sustained-release collapse-preserving mother solution, and a polycarboxylic acid late-term sustained-release collapse-preserving mother solution, and the mass concentration is 40 wt%.

[0014] Furthermore, the mass ratio of sodium gluconate to white sugar in the retarder is 50-70:30-50.

[0015] Furthermore, the viscosity reducing admixtures are polycarboxylic acid water reducing mother liquor, polycarboxylic acid phosphate viscosity reducing mother liquor, polycarboxylic acid medium-term sustained-release collapse-preserving mother liquor and polycarboxylic acid late-stage sustained-release collapse-preserving mother liquor, and the number average molecular weights are 44000-47000, 32000-35000, 35000-37000 and 32000-34000 respectively.

[0016] Furthermore, the carbonization inhibition auxiliary agent is a mixture of perhydropolysilazane and hydrophilic nano-silica in a mass ratio of 20-35:65-80.

[0017] Furthermore, the functional defoamer is a liquid mixture of a polyether-modified silicone defoamer and hydrophobic nano-silica in a mass ratio of 50-65:35-50.

[0018] Furthermore, the concentration of the functional defoamer is 0.5 wt %.

[0019] The present invention also provides a method for preparing the above-mentioned high-strength white facing concrete, comprising the following steps:

[0020] (1) white cement and white high-activity mineral admixture are mixed to obtain a mixed adhesive; a viscosity-reducing admixture, a functional defoamer and 70% of water are mixed to obtain a mixed solution A; a carbonization inhibition auxiliary agent and the remaining water are ultrasonically dispersed for 60-120 seconds to obtain a mixed solution B;

[0021] (2) The mixed adhesive obtained in step (1), limestone machine-made sand and limestone crushed stone are mixed and stirred for 30-45 seconds, then the mixed solution A obtained in step (1) is added and stirred for 50-75 seconds, and then the mixed solution B obtained in step (1) is added and stirred for 30-45 seconds to obtain high-strength white facing concrete.

[0022] The present invention has the following beneficial effects:

[0023] 1. In the high-strength white facing concrete of the present invention, the polycarboxylic acid water-reducing mother liquid (number average molecular weight 44000-47000) and polycarboxylic acid phosphate viscosity-reducing mother liquid (number average molecular weight 32000-35000) in the viscosity-reducing admixture have special hydrophobic groups in structure to form a hydrophobic solvation layer on the surface of cement particles. The hydrophilic solvation layer composed of the side chain of polyoxyethylene ether and the two together will form a water film layer with a certain mechanical strength on the surface of cement particles, which can release the free water between cement particles, help to destroy the floc structure of cement particles, and improve the lubrication between cement particles and aggregates; wherein, the phosphate group in the phosphate ester has a high charge density and a high resistance to Ca 2+ The complexation enhances the adsorption of cement particles. The stable polycarboxylate water-reducing agent adsorption layer on the surface of cement particles can effectively reduce the interaction between cement particles. The presence of phosphate groups can reduce the surface tension of the water-reducing agent, which is beneficial to the reduction of the water film thickness of the adsorption layer, release more free water, and thus reduce the viscosity of the cement paste. The ester groups of the polycarboxylate medium-term sustained-release slump-retaining mother solution (number average molecular weight 35000-37000) and the polycarboxylate late-term sustained-release slump-retaining mother solution (number average molecular weight 32000-34000) are used in combination due to their different hydrolysis and release times and stable release. The ester groups of the medium-term sustained-release slump-retaining mother solution (number average molecular weight 35000-37000) begin to release slowly at 1 hour, reach a peak at 3 hours, and release steadily without amplification during the process. The ester groups of the polycarboxylate late-term sustained-release slump-retaining mother solution (number average molecular weight 32000-34000) begin to release at 3 hours, reach a peak at 4 hours, do not amplify at 3-4 hours, and have certain losses at 5 hours. Ensure the working stability of concrete within 5 hours, meet construction requirements, and facilitate production control. Use the retarder in the viscosity-reducing admixture to control concrete hydration, inhibit the influence of concrete hydration on concrete collapse resistance, and facilitate concrete construction.

[0024] 2. The perhydropolysilazane in the carbonization inhibition auxiliary agent has a hydrophilic group, but it is insoluble in water. The hydrophilic group of perhydropolysilazane can generate hydrogen bonds with water molecules, thereby locking water molecules. At the same time, perhydropolysilazane can prevent the hydrogen and oxygen elements in the concrete from being captured, thereby preventing carbonization and keeping the concrete mud white. Nano-silicon dioxide particles are fine, one is to fill micropores. The other is to be in alkaline and Ca 2+ Under the action of CSH gel, it further fills the dense pores, prevents water molecules from escaping, blocks the carbonization reaction of air CO2 and Ca(OH)2 in concrete, and keeps the concrete white. When the two are used together, hydrogen polysilazane locks water and prevents the hydrogen and oxygen elements in concrete from being captured, providing water and alkaline Ca for the secondary hydration reaction of hydrophilic nano-silica. 2+ environment, producing more CSH gel filling, further reducing the porosity and further improving the carbonation resistance of concrete.

[0025] 3. Use the polyether-modified silicone defoamer and hydrophobic nano-silica in the functional defoamer to effectively control the bubbles in the concrete. First, the polyether-modified silicone defoamer is mainly composed of polyether with strong anti-foaming ability and dimethyl silicone oil with strong hydrophobicity and rapid bubble breaking. It has the characteristics of low surface tension, rapid defoaming, and long anti-foaming time, and has a good effect on eliminating bubbles in concrete. Second, the hydrophobic nano-silica has a small particle size and high surface energy, which enables it to form a huge force to adsorb bubbles. The "needle tip" effect of nano-silica adsorbs and impacts bubbles to create weak points and accelerate the rupture of bubbles. Third, polyether-modified silicone and hydrophobic nano-silica together attack the bubbles. With the presence of hydrophobic nano-silica, polyether-modified silicone can diffuse faster on the air-water interface in the foaming liquid, improve the dispersion efficiency of polyether-modified silicone, and improve the efficiency of bubble elimination.

[0026] 4. The high-strength white facing concrete of the present invention is beautiful and has good decorative effect. It eliminates the processes of coating and finishing, meets the needs of low-carbon green development, and effectively solves the problems of concrete bubbles, inconsistent color, voids, cracks and poor carbonation resistance in the prior art. DETAILED DESCRIPTION

[0027] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific conditions are specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.

[0028] Example 1

[0029] A high-strength white facing concrete, comprising white cement, white high-activity mineral admixture, limestone machine-made sand, limestone crushed stone, water, a viscosity-reducing admixture, a carbonation inhibition auxiliary agent and a functional defoaming agent;

[0030] The mass ratio of white cement, white high-activity mineral admixture, limestone machine-made sand, limestone crushed stone, water, viscosity-reducing admixture, carbonation inhibition auxiliary agent and functional defoaming agent is 400:80:650:1150:160:10.5:4:0.9.

[0031] The white cement is white silicate cement, PW-1 42.5, whiteness value ≥ 89. The limestone crushed stone is a continuous graded particle size of 5.0-25.0 mm, and the mud content is ≤ 0.1%.

[0032] The method for preparing the above-mentioned high-strength white facing concrete comprises the following steps:

[0033] (1) white cement and white high-activity mineral admixture are mixed to obtain a mixed adhesive; a viscosity-reducing admixture, a functional defoamer and 70% of water are mixed to obtain a mixed solution A; a carbonization inhibition auxiliary agent and the remaining water are ultrasonically dispersed by 90 to obtain a mixed solution B;

[0034] (2) The mixed adhesive material, limestone machine-made sand and limestone crushed stone obtained in step (1) are mixed and stirred for 40 minutes, then the mixed solution A obtained in step (1) is added and stirred for 60 minutes, and then the mixed solution B obtained in step (1) is added and stirred for 40 minutes to obtain a high-strength white facing concrete.

[0035] The preparation methods of Examples 2-4, Comparative Examples 1-12 and the control group are the same as that of Example 1, and the amounts of the components are shown in Table 1.

[0036] Table 1 Component dosage of Examples 1-4, Comparative Examples 1-12 and Control Group

[0037]

[0038]

[0039] Note: The admixtures used in the control group are common admixtures commonly used in this field.

[0040] The white high-activity mineral admixture, viscosity-reducing admixture, carbonization inhibition auxiliary agent and functional defoaming agent are shown in Table 2-5 respectively.

[0041] Table 2 Composition of white high-activity mineral admixture

[0042] White phosphorus slag powder White S95 mineral powder White silica ash Control group 20 50 30 Example 1 20 50 30 Example 2 30 40 30 Example 3 40 40 20 Example 4 40 50 10 Comparative Example 1 20 50 30 Comparative Example 2 20 50 30 Comparative Example 3 20 50 30 Comparative Example 4 20 50 30 Comparative Example 5 20 50 30 Comparative Example 6 20 50 30 Comparative Example 7 20 50 30 Comparative Example 8 20 50 30 Comparative Example 9 20 50 30 Comparative Example 10 20 50 30 Comparative Example 11 20 50 30 Comparative Example 12 20 50 30

[0043] Table 3 Composition of viscosity reducing admixtures

[0044]

[0045]

[0046] Table 4 Carbonization inhibition auxiliary agent composition table

[0047] Perhydropolysilazane Hydrophilic Nano Silica Example 1 20 80 Example 2 25 75 Example 3 30 70 Example 4 35 65 Comparative Example 1 20 80 Comparative Example 2 20 80 Comparative Example 3 20 80 Comparative Example 4 20 80 Comparative Example 5 20 80 Comparative Example 6 20 80 Comparative Example 7 20 80 Comparative Example 8 20 80 Comparative Example 9 0 100 Comparative Example 10 100 0 Comparative Example 11 20 80 Comparative Example 12 20 80

[0048] Table 5 Functional defoamer ingredients

[0049]

[0050]

[0051] The concrete obtained from Example 14, Comparative Examples 1-12 and the control group was subjected to expansion, slump and rapid carbonation tests. The results are shown in Table 6.

[0052] Table 6 Concrete performance statistics

[0053]

[0054]

[0055] As shown in Table 6, the expansion, slump and carbonization of the concrete obtained in Examples 1-4 all meet the requirements and are better than the control group and Comparative Examples 1-12. Compared with Example 1, Comparative Examples 1-4 use polycarboxylic acid water-reducing mother solution (number average molecular weight 44000-47000), polycarboxylic acid phosphate viscosity-reducing mother solution (number average molecular weight 32000-35000), polycarboxylic acid medium-term sustained-release slump-retaining mother solution (number average molecular weight 35000-37000), and polycarboxylic acid late-stage sustained-release slump-retaining mother solution (number average molecular weight 32000-34000) alone, but the workability, slump-retaining property and carbonization resistance are poor, which do not meet the requirements. Compared with Example 1, the viscosity-reducing admixtures of Comparative Examples 5-8 lack one of the following components: polycarboxylic acid water-reducing mother liquor (number average molecular weight 44000-47000), polycarboxylic acid phosphate viscosity-reducing mother liquor, polycarboxylic acid phosphate viscosity-reducing mother liquor (number average molecular weight 32000-35000), polycarboxylic acid medium-term sustained-release slump-retaining mother liquor (number average molecular weight 35000-37000), and polycarboxylic acid late-stage sustained-release slump-retaining mother liquor (number average molecular weight 32000-34000). The same results showed poor workability, poor slump-retaining property, poor carbonization resistance, etc., which did not meet the requirements. It can be seen from the side that the synergistic effect of the four components in the viscosity-reducing admixture effectively improves the performance of concrete. Compared with Example 1, when perhydropolysilazane and hydrophilic nano-silica were used alone, the carbonization depth of concrete was still large. This shows that the synergistic effect of perhydropolysilazane and hydrophilic nano-silica improves the carbonation resistance of concrete. Compared with Example 1, the defoaming effect of Comparative Examples 11-12 is still poor, while Example 1 has good defoaming and foam suppression. This shows that the functional defoamer composed of polyether-modified silicone defoamer and hydrophobic nano-silica has good defoaming and foam suppression effects and can work for a long time.

[0056] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A high-strength white facing concrete, characterized in that: Including white cement, white high-activity mineral admixture, limestone machine-made sand, limestone crushed stone, water, viscosity-reducing admixture, carbonation inhibition auxiliary agent and functional defoamer; The mass ratio of the white cement, white high-activity mineral admixture, limestone machine-made sand, limestone crushed stone, water, viscosity-reducing admixture, carbonization inhibition auxiliary agent and functional defoamer is 400-480:50-80:580-700:1100-1160:160-164:10.5-12:4-6:0.9-1.2; The viscosity-reducing admixture is prepared by compounding polycarboxylic acid water-reducing mother liquor, polycarboxylic acid phosphate viscosity-reducing mother liquor, polycarboxylic acid medium-term sustained-release slump-retaining mother liquor, polycarboxylic acid late-term sustained-release slump-retaining mother liquor and retarder in a mass ratio of 35-45:20-30:5-10:10-20:10-20; the number average molecular weights of polycarboxylic acid water-reducing mother liquor, polycarboxylic acid phosphate viscosity-reducing mother liquor, polycarboxylic acid medium-term sustained-release slump-retaining mother liquor and polycarboxylic acid late-term sustained-release slump-retaining mother liquor are 44000-47000, 32000-35000, 35000-37000 and 32000-34000 respectively; The carbonization inhibition auxiliary agent is a mixture of perhydropolysilazane and hydrophilic nano-silica in a mass ratio of 20-35:65-80; the functional defoamer is a liquid mixture of polyether-modified silicone defoamer and hydrophobic nano-silica in a mass ratio of 50-65:35-50.

2. The high-strength white facing concrete according to claim 1, characterized in that: The white cement is white silicate cement, PW-1 42.5, whiteness value ≥89.

3. The high-strength white facing concrete according to claim 1, characterized in that: The white high-activity mineral admixture is a solid mixed powder formed by mixing white phosphorus slag powder, white S95 mineral powder and white silica fume in a mass ratio of 20-40:20-50:10-30.

4. The high-strength white facing concrete according to claim 1, characterized in that: The limestone machine-made sand has an MB value of ≤0.8, a fineness modulus of 2.9-3.3, a particle size of less than 80 μm ≤3.0%, and a mud content rate of ≤0.1%.

5. The high-strength white facing concrete according to claim 1, characterized in that: The limestone crushed stone has a continuous gradation with a particle size of 5.0-25.0 mm and a mud content of ≤0.1%.

6. The method for preparing the high-strength white facing concrete according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Mix white cement and white high-activity mineral admixture to obtain a mixed adhesive; mix the viscosity-reducing admixture, functional defoamer and 70% water to obtain a mixed solution A; ultrasonically disperse the carbonization inhibition auxiliary agent and the remaining water for 60-120 seconds to obtain a mixed solution B; (2) The mixed adhesive obtained in step (1), limestone machine-made sand and limestone crushed stone are mixed and stirred for 30-45 seconds, then the mixed solution A obtained in step (1) is added and stirred for 50-75 seconds, and then the mixed solution B obtained in step (1) is added and stirred for 30-45 seconds to obtain high-strength white facing concrete.

Citation Information

Patent Citations

  • Cement-based polycarboxylate superplasticizer mother liquor with ultralong-acting slump loss resistance and application thereof

    CN110938176A

  • Synthesis method of viscosity reduction type phosphate polycarboxylic acid water reducing agent and prepared water reducing agent

    CN112920335A

  • White bare concrete and preparation method thereof

    CN116835942A